2012
DOI: 10.1371/journal.ppat.1003072
|View full text |Cite|
|
Sign up to set email alerts
|

Clostridium difficile Toxin B Causes Epithelial Cell Necrosis through an Autoprocessing-Independent Mechanism

Abstract: Clostridium difficile is the most common cause of antibiotic-associated nosocomial infection in the United States. C. difficile secretes two homologous toxins, TcdA and TcdB, which are responsible for the symptoms of C. difficile associated disease. The mechanism of toxin action includes an autoprocessing event where a cysteine protease domain (CPD) releases a glucosyltransferase domain (GTD) into the cytosol. The GTD acts to modify and inactivate Rho-family GTPases. The presumed importance of autoprocessing i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
132
1
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 112 publications
(145 citation statements)
references
References 44 publications
11
132
1
1
Order By: Relevance
“…Several recent studies have shown that under certain conditions, the glucosyltransferase domain (10), the cysteine protease domain (10,32), and even the receptorbinding domain (33) are dispensable for function. Our panel of pore-defective mutants identified here, uniquely allowed us to test the importance of translocation domain function in toxin function.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Several recent studies have shown that under certain conditions, the glucosyltransferase domain (10), the cysteine protease domain (10,32), and even the receptorbinding domain (33) are dispensable for function. Our panel of pore-defective mutants identified here, uniquely allowed us to test the importance of translocation domain function in toxin function.…”
Section: Discussionmentioning
confidence: 99%
“…Cell death assay was performed as previously described (10). Assay plates were read in Spectramax M5 plate reader (Molecular Devices).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations